Long‐term survival outcomes of cytoreductive surgery and perioperative intraperitoneal chemotherapy: Single‐institutional experience with 1225 cases. Issue 4 (16th July 2019) - Kyang, Lee Shyang; Alzahrani, Nayef A.; Valle, Sarah J.; Rahman, Mohamed K.; Arrowaili, Arif; Liauw, Winston; Morris, David L.
Abstract: Background and Objectives: To review long‐term survival outcomes of patients with Peritoneal metastasis (PM) who underwent colorectal cancer (CRS) and intraperitoneal chemotherapy (PIC). Methods: Patients that underwent CRS, with or without PIC, from January 1996 to March 2018 at the Peritonectomy Unit of St. George Hospital, Sydney were retrospectively analyzed from a prospectively maintained database. Results: The study comprised of 1225 cases, including 687 females (56.1%) and 538 males (43.9%). Diagnoses included CRC (n = 363), followed by HAMN (n = 317), LAMN (n = 297), mesothelioma (n = 101), ovarian cancer (n = 55), and others including gastric, sarcoma, and neuroendocrine tumor (n = 92). The median OS, 5‐ and 10‐year survivals for CRC were 35 months, 33% and 8%, respectively. Patients with LAMN, in relative to HAMN, experienced a higher median OS, 5‐ and 10‐year survivals (248 months vs 63 months; 82% vs 52% and 59% vs 28%). The median OS for mesothelioma was 60 months with 5‐ and 10‐year survivals of 48% and 19%, respectively. In ovarian cancer, the median OS was 30 months with 5‐ and 10‐year survivals of 26% and 10%, respectively. For the remaining histological diagnoses, median OS and 5‐year survival were 28 months and 27%, respectively. Conclusion: Our large‐cohort data showed that CRS/PIC can provide long‐term survival benefit to patients with PM of gastrointestinal and ovarian origin.